Mathematical Induction - Questions and Solutions

Question 1
Important
Deleted for CBSE Board 2025 Exams

Question 2 Deleted for CBSE Board 2025 Exams

Question 3 Important Deleted for CBSE Board 2025 Exams

Question 4 Deleted for CBSE Board 2025 Exams

Question 5 Important Deleted for CBSE Board 2025 Exams

Question 6 Deleted for CBSE Board 2025 Exams

Question 7 Important Deleted for CBSE Board 2025 Exams

Question 8 Important Deleted for CBSE Board 2025 Exams

Question 9 Deleted for CBSE Board 2025 Exams

Question 10 Deleted for CBSE Board 2025 Exams

Question 11 Important Deleted for CBSE Board 2025 Exams

Question 12 Deleted for CBSE Board 2025 Exams You are here

Question 13 Important Deleted for CBSE Board 2025 Exams

Question 14 Deleted for CBSE Board 2025 Exams

Question 15 Important Deleted for CBSE Board 2025 Exams

Question 16 Important Deleted for CBSE Board 2025 Exams

Question 17 Important Deleted for CBSE Board 2025 Exams

Question 18 Important Deleted for CBSE Board 2025 Exams

Question 19 Deleted for CBSE Board 2025 Exams

Question 20 Deleted for CBSE Board 2025 Exams

Question 21 Important Deleted for CBSE Board 2025 Exams

Question 22 Deleted for CBSE Board 2025 Exams

Question 23 Important Deleted for CBSE Board 2025 Exams

Question 24 Important Deleted for CBSE Board 2025 Exams

Mathematical Induction

Serial order wise

Last updated at April 16, 2024 by Teachoo

Question 12: Prove the following by using the principle of mathematical induction for all n ∈ N: a + ar + ar2 + ……..+ arn – 1 = (𝑎(𝑟^𝑛 − 1))/(𝑟 − 1) Let P (n) : a + ar + ar2 + ……..+ arn – 1 = 𝑎(𝑟^𝑛 − 1)/(𝑟 − 1) For n = 1, L.H.S = a R.H.S = (𝑎(𝑟1 − 1))/(𝑟 − 1) = (𝑎(𝑟 − 1))/(𝑟 − 1) = a L.H.S. = R.H.S ∴ P(n) is true for n = 1 Assume that P(k) is true a + ar + ar2 + ……..+ ark – 1 = 𝑎(𝑟^𝑘 − 1)/(𝑟 − 1) We will prove that P(k + 1) is true. a + ar + ar2 + ……..+ ar(k + 1) – 1 = 𝑎(𝑟^(𝑘 + 1) − 1)/(𝑟 − 1) a + ar + ar2 + ……..+ ark – 1 + ark = 𝑎(𝑟^(𝑘 + 1) − 1)/(𝑟 − 1) We have to prove P(k+1) from P(k) i.e. (2) from (1) From (1) a + ar + ar2 + ……..+ ark – 1 = 𝑎(𝑟^𝑘 − 1)/(𝑟 − 1) Adding ark both sides a + ar + ar2 + …….. +ark – 1 + ark = 𝑎(𝑟^𝑘 − 1)/(𝑟 − 1) + ark = (𝑎(𝑟^𝑘 − 1) + (𝑟 − 1)𝑎𝑟^𝑘)/(𝑟 − 1) = (𝑎𝑟^𝑘 − 𝑎 + 𝑎𝑟^𝑘 (𝑟) − 𝑎𝑟^𝑘)/(𝑟 − 1) = (𝑎𝑟^𝑘− 𝑎𝑟^𝑘 − 𝑎 + 𝑎𝑟^𝑘 (𝑟))/(𝑟 − 1) = (0 − 𝑎 + 𝑎𝑟^𝑘 (𝑟))/(𝑟 − 1) = (− 𝑎 + 𝑎𝑟^𝑘 (𝑟))/(𝑟 − 1) = (− 𝑎 + 𝑎𝑟^𝑘 (𝑟^1 ))/(𝑟 − 1) = (− 𝑎 + 𝑎𝑟^(𝑘 + 1))/(𝑟 − 1) = (𝑎 (−1 + 𝑟^(𝑘 + 1) ))/(𝑟 − 1) = 𝑎(𝑟^(𝑘 + 1) − 1)/(𝑟 − 1) Thus, a + ar + ar2 + ……..+ ark – 1 + ark = 𝑎(𝑟^(𝑘 + 1) − 1)/(𝑟 − 1) which is the same as P(k + 1) ∴ P(k + 1) is true whenever P(k) is true. ∴ By the principle of mathematical induction, P(n) is true for n, where n is a natural number